Intragranular b-axis shortened grade pore ZSM-5 molecular sieve as well as preparation method and application thereof

By introducing a highly interconnected macropore-mesoporous hierarchical structure into the ZSM-5 molecular sieve and utilizing the structural guidance and corrosion effects of tetrapropylammonium hydroxide, in-situ corrosion-recrystallization is performed to synthesize a hierarchical pore ZSM-5 molecular sieve with a shortened b-axis within the crystal, thus solving the diffusion limitation problem and improving the catalytic performance and life.

CN120717484APending Publication Date: 2025-09-30WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510809215.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

The existing ZSM-5 molecular sieve has low utilization of catalytic active sites due to diffusion limitations in the methanol to olefins process, and the traditional hierarchical pore synthesis method is complex and expensive, making it difficult to apply on a large scale.

Method used

By introducing a highly interconnected macropore-mesoporous hierarchical structure into the ZSM-5 molecular sieve and using tetrapropylammonium hydroxide as a structure-directing agent and corrosive agent, a hierarchical pore ZSM-5 molecular sieve with a shortened b-axis within the crystal is synthesized by in-situ corrosion-recrystallization, thus avoiding the defects of traditional methods.

Benefits of technology

The b-axis diffusion distance within the zeolite is significantly shortened, the double-leak selectivity and catalytic life of the catalyst are improved, the catalytic performance is enhanced, and the diffusion limitation problem of traditional ZSM-5 zeolite in the methanol to olefins process is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120717484A_ABST
    Figure CN120717484A_ABST
Patent Text Reader

Abstract

The invention discloses an intragranular b-axis shortened grade pore ZSM-5 molecular sieve and a preparation method thereof, urea is dissolved in a mixed solution of tetrapropylammonium hydroxide and deionized water, tetraethyl orthosilicate is dropwise added, and continuous stirring hydrolysis is performed until clarification to obtain a Silicalite-1 molecular sieve precursor solution; transferring the obtained precursor solution into a stainless steel high-pressure reaction kettle with a polytetrafluoroethylene lining, carrying out hydrothermal crystallization treatment, and carrying out suction filtration and drying to obtain a pure silicon molecular sieve Silicalite-1 solid product; carrying out high-temperature roasting in the air to obtain a tabulate Silicalite-1 molecular sieve; dissolving aluminum isopropoxide in a tetrapropylammonium hydroxide aqueous solution, mixing with the obtained flat-plate-shaped Silicalite-1 molecular sieve, carrying out homogeneous hydrothermal crystallization treatment, and carrying out suction filtration and drying to obtain a silicon-aluminum molecular sieve ZSM-5 solid product; and roasting in air to obtain a final product. The product comprises a highly through hollow macroporous-mesoporous-microporous hierarchical structure; the overall size of the nanosheet is as follows: a: b: c = (600 to 800): (120 to 180): (4000 to 7000) nm; the shortest intra-crystal b-axis diffusion length lt; and the wavelength is 50 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a ZSM-5 molecular sieve and a preparation method and application thereof. Background Art

[0002] Light olefins, particularly ethylene and propylene, are important components and key raw materials for the petrochemical industry. The methanol-to-olefins (MTO) process offers a non-petroleum-based pathway for the selective production of light olefins in a post-petroleum society, as methanol can be readily obtained from alternative carbon sources such as coal, natural gas, and biomass. ZSM-5 zeolite catalysts, due to their unique MFI (Methyl Inert Fluorinated Fractional Initiator) ten-membered ring topology and abundant acid-active site distribution, combined with their high resistance to deactivation by coke deposition, are considered among the most suitable catalytic materials for industrial MTO. However, low light olefin selectivity still limits the further application of ZSM-5 zeolites in MTO processes. This is primarily due to the difficulty of methanol and its autocatalytically formed hydrocarbon pool species (primarily large olefins and cyclic organic species) to rapidly diffuse into and out of the single MFI micropore channels, significantly reducing the utilization of the acid-active sites in the ZSM-5 zeolite. Therefore, the development of ZSM-5 zeolite catalysts with enhanced diffusion capacity is urgently needed.

[0003] The preparation of nanomolecular sieves and hierarchical pore molecular sieves are two main strategies to improve the diffusion capacity of molecular sieve crystals. Nanomolecular sieves shorten the diffusion path along all crystal plane orientations by reducing the particle size. However, low crystallinity, easy agglomeration and difficult separation are inevitable disadvantages of nanomolecular sieves. In contrast, the introduction of hierarchical pore structure in molecular sieve crystals is considered to be a more effective strategy, which can improve the mass transfer capacity of molecular sieves without losing the selective effect on the size and shape of guest molecules. The introduction of hierarchical pores can shorten the diffusion length, especially along the MFI. b The diffusion length in the axial direction can significantly improve the diffusion performance of this type of molecular sieve.

[0004] The current synthesis strategies of hierarchical pore molecular sieves usually involve expensive organic surfactants and complex template preparation and removal steps, which greatly limits their large-scale preparation. Therefore, it is necessary to develop a simple and scalable preparation method to directly synthesize intracrystalline b The development of hierarchical pore ZSM-5 zeolite catalytic materials with significantly shortened axial diffusion length (especially when the length is <50 nm, the diffusion limitation will be greatly alleviated) still faces great challenges. Summary of the Invention

[0005] One of the purposes of the present invention is to provide an intracrystalline bThe highly through-hole ZSM-5 molecular sieve with shortened axis is obtained by introducing a highly through-hole macropore-mesoporous hierarchical structure into the flat molecular sieve. b Axial diffusion distance is significantly shortened (minimum b ZSM-5 molecular sieve with hierarchical pore size (axis length <50 nm).

[0006] An intracrystalline b The hierarchical pore ZSM-5 molecular sieve with shortened axis is a single crystal nanosheet comprising a highly interconnected hollow macropore-mesopore-micropore hierarchical structure; the overall size of the nanosheet is a : b : c = (600~800): (120~180): (4000~7000) nm; shortest intracrystalline b Axis diffusion length <50 nm.

[0007] The second object of the present invention is to provide the above-mentioned intracrystalline b The preparation method of the highly through-graded ZSM-5 zeolite with shortened axes avoids the damage to the topological structure and crystallinity of the zeolite by the traditional corrosion process, and effectively solves the difficult problems of using expensive organic additives and complex template removal steps in the traditional in-situ method.

[0008] The above-mentioned intracrystalline b The preparation method of the hierarchical pore ZSM-5 molecular sieve with shortened axis comprises the following steps: (1) Dissolve urea in a mixed solution of tetrapropylammonium hydroxide and deionized water, add tetraethyl orthosilicate dropwise and continue stirring to hydrolyze until clear to obtain a Silicalite-1 molecular sieve precursor solution; (2) The obtained precursor solution was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and after hydrothermal crystallization, the solid product of pure silicon molecular sieve Silicalite-1 was obtained by filtration and drying; (3) The obtained pure silicon molecular sieve Silicalite-1 solid product is calcined at high temperature in air to obtain a flat Silicalite-1 molecular sieve; (4) Aluminum isopropoxide is dissolved in a tetrapropylammonium hydroxide aqueous solution, mixed with the obtained flat Silicalite-1 molecular sieve, and transferred into a stainless steel high-pressure reactor equipped with a polytetrafluoroethylene liner. After homogeneous hydrothermal crystallization, the mixture is filtered and dried to obtain a solid product of silicon aluminum molecular sieve ZSM-5; (5) The obtained solid product of silicon-alumina molecular sieve ZSM-5 is calcined in air to obtain the crystal b Axially shortened hierarchical pore ZSM-5 molecular sieve single crystal nanosheets.

[0009] According to the above scheme, the molar ratio of urea, tetrapropylammonium hydroxide, deionized water and tetraethyl orthosilicate in step 1 is (0.3~0.5): (0.15~0.21): (15~25): 1.

[0010] According to the above scheme, the stirring hydrolysis temperature in step 1 is 10~50℃ and the time is 5~10 h.

[0011] According to the above scheme, the crystallization temperature of the hydrothermal crystallization treatment in step 2 is 160~200℃, and the crystallization time is 48~72h.

[0012] According to the above scheme, in step 3, the calcination process is heated to 500-600°C at a rate of 1-5°C / min and kept at this temperature for 5-10 h.

[0013] According to the above scheme, the concentration of the tetrapropylammonium hydroxide aqueous solution in step 4 is 0.1~0.3 M; the mass ratio of the isopropyl aluminum solution to the flat Silicalite-1 molecular sieve is between (0.005~0.05):1; and the liquid-to-solid ratio of the tetrapropylammonium hydroxide aqueous solution to the flat Silicalite-1 molecular sieve is between (70~90):1 mL / g.

[0014] According to the above scheme, the crystallization temperature of the homogeneous hydrothermal crystallization treatment in step 4 is 160~200℃, and the crystallization time is 24~48 h.

[0015] According to the above scheme, in step 5, the calcination process is heated to 500-600°C at a rate of 1-5°C / min and kept at this temperature for 5-10 h.

[0016] The third object of the present invention is to provide the above-mentioned intracrystalline b The application of highly through-graded ZSM-5 molecular sieve with shortened axis in the catalytic reaction of methanol to olefins has achieved significant improvements in double olefin selectivity and catalytic life compared with traditional micron ZSM-5 molecular sieve.

[0017] Compared with the prior art, the present invention has the following beneficial effects: First, compared with other hierarchical pore ZSM-5 molecular sieve catalytic materials, the present invention realizes the high-throughput macropore-mesopore-micropore hierarchical structure in a single molecular sieve crystal by introducing a highly interconnected macropore-mesopore-micropore hierarchical structure into the flat molecular sieve. b Axial diffusion distance is significantly shortened (minimum b Preparation of hierarchical pore ZSM-5 molecular sieve with axis length <50 nm. b The diffusion capacity of the axial straight channel often determines the catalytic performance of the entire material. Therefore, the intracrystalline bThe highly interpenetrating hierarchical pore molecular sieve ZSM-5 single crystal nanosheets with shortened axes will undoubtedly have obvious catalytic advantages and industrial application potential, and have initially demonstrated significantly enhanced catalytic performance in the methanol to olefins catalytic reaction: 63.5% double olefin selectivity (an increase of 19% compared to traditional micron ZSM-5 molecular sieves) and 22.2 h of catalytic life (an increase of 6.5 times compared to traditional micron ZSM-5 molecular sieves).

[0018] Secondly, compared with other short b The synthesis method of axial grade pore ZSM-5 molecular sieve innovatively utilizes the structural guidance and corrosion effect of tetrapropylammonium hydroxide, uses the flat Silicalite-1 molecular sieve as a template and silicon source at the same time, and makes OH - The etched Silicalite-1 molecular sieve framework silicon species and the additional introduced aluminum species re-crystallize around the flat etched structure, thereby synthesizing the intracrystalline b Highly interconnected hierarchical pore molecular sieve ZSM-5 single crystal nanosheets with significantly shortened axial diffusion length.

[0019] While revealing the mechanism and steps of the in-situ corrosion-recrystallization process, the present invention also effectively avoids the damage to the topological structure and crystallinity of the molecular sieve by the traditional corrosion process, and solves the problem of using expensive organic additives or complex template removal steps in the traditional in-situ method. The present invention addresses the major problems of ZSM-5 catalyst in methanol conversion industry catalysis, such as short life, low activity and easy carbon deposition and deactivation. It involves ① intracrystalline with enhanced diffusion ability b ② The axially shortened graded pore ZSM-5 zeolite catalytic material and ② the corrosion-recrystallization synthesis strategy with simple and easy-to-scale characteristics are expected to meet the current market demand. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The crystal prepared in Example 1 b Scanning electron microscope image of the axis-shortened hierarchical pore ZSM-5 molecular sieve. The results show that the synthesized hierarchical pore ZSM-5 molecular sieve exhibits a uniform nanosheet morphology as a whole.

[0021] Figure 2 The crystal prepared in Example 1 b Transmission electron microscope image of the axis-shortened hierarchical pore ZSM-5 molecular sieve. The results show that the synthesized hierarchical pore ZSM-5 molecular sieve has a rich intracrystalline macropore-mesoporous structure, and the additionally introduced macropore-mesoporous pores have extremely strong connectivity with the MFI intrinsic micropores.

[0022] Figure 3 The crystal prepared in Example 1 bThe selected area electron diffraction image of the axis-shortened hierarchical pore ZSM-5 molecular sieve shows that the synthesized hierarchical pore ZSM-5 molecular sieve has discrete single crystal diffraction spots along the

[010] axis of typical MFI type molecular sieves.

[0023] Figure 4 The crystal prepared in Example 1 b The X-ray diffraction pattern of the axially shortened hierarchical pore ZSM-5 zeolite shows that the synthesized hierarchical pore ZSM-5 zeolite has the typical characteristic diffraction peaks of MFI type zeolite.

[0024] Figure 5 The crystal prepared in Example 1 b The N2 adsorption-desorption isotherms of the axis-shortened hierarchical pore ZSM-5 zeolite show that the synthesized hierarchical pore ZSM-5 zeolite has both abundant microporous structures (P / P0<0.01) and a large number of corroded macropores and mesoporous structures (0.45 <P / P0<0.99)。

[0025] Figure 6 The crystal prepared in Example 1 b The Si NMR spectrum of the axis-shortened hierarchical pore ZSM-5 molecular sieve shows that the synthesized hierarchical pore ZSM-5 molecular sieve mainly contains Q 4 Silicon Si(OSi)4 species, high degree of polycondensation.

[0026] Figure 7 The crystal prepared in Example 1 b The aluminum NMR spectrum of the axis-shortened hierarchical pore ZSM-5 zeolite shows that all Al species in the synthesized hierarchical pore ZSM-5 zeolite are successfully incorporated into the zeolite framework and form tetrahedral aluminum AlO 4- Form exists.

[0027] Figure 8 The low Si / Al crystal prepared in Example 2 b Transmission electron microscope image of the axis-shortened hierarchical pore ZSM-5 molecular sieve. The results show that the synthesized hierarchical pore ZSM-5 molecular sieve has a uniform nanosheet morphology and a rich intracrystalline through-hole macropore-mesopore-micropore hierarchical structure.

[0028] Figure 9 The low Si / Al crystal prepared in Example 2 b The X-ray diffraction pattern of the axially shortened hierarchical pore ZSM-5 zeolite shows that the synthesized hierarchical pore ZSM-5 zeolite has the typical characteristic diffraction peaks of MFI type zeolite.

[0029] Figure 10 The high Si / Al crystal prepared in Example 3 bTransmission electron microscope image of the axis-shortened hierarchical pore ZSM-5 molecular sieve. The results show that the synthesized hierarchical pore ZSM-5 molecular sieve has a uniform nanosheet morphology and a rich intracrystalline through-hole macropore-mesopore-micropore hierarchical structure.

[0030] Figure 11 The high Si / Al crystal prepared in Example 3 b The X-ray diffraction pattern of the axially shortened hierarchical pore ZSM-5 zeolite shows that the synthesized hierarchical pore ZSM-5 zeolite has the typical characteristic diffraction peaks of MFI type zeolite.

[0031] Figure 12 The SEM image of the hierarchical pore ZSM-5 molecular sieve nanoparticles prepared in Comparative Example 1 shows that the synthesized hierarchical pore ZSM-5 molecular sieve nanoparticles have uniform grain size and abundant intracrystalline through-grade pore structure, but exhibit a significantly shortened MFI. c Axis length.

[0032] Figure 13 This is the X-ray diffraction pattern of the hierarchical pore ZSM-5 molecular sieve nanoparticles prepared in Comparative Example 1. The results show that the synthesized hierarchical pore ZSM-5 molecular sieve nanoparticles have typical MFI type molecular sieve characteristic diffraction peaks.

[0033] Figure 14 This is a scanning electron microscope image of the nano ZSM-5 molecular sieve prepared in Comparative Example 2. The results show that the synthesized nano ZSM-5 molecular sieve has a uniform grain size.

[0034] Figure 15 This is a scanning electron microscope image of the micron ZSM-5 molecular sieve prepared in comparative example 3. The results show that the synthesized micron ZSM-5 molecular sieve exhibits MFI as a whole. b Uniform coffin-like morphology with significantly increased shaft thickness. DETAILED DESCRIPTION

[0035] The present invention is further described below with reference to the accompanying drawings and examples. However, the present invention is not limited to the following methods. In the specific embodiments, unless otherwise specified, the reagents described are all commercially available chemical reagents.

[0036] Example 1 An intracrystalline b Preparation method of single crystal nanosheets of highly through-graded molecular sieve ZSM-5 with shortened axis: (1) Dissolve 0.96 g of urea in a mixed solution of 3.60 g of 2.0 M tetrapropylammonium hydroxide and 10.82 g of deionized water, add 8.33 g of tetraethyl orthosilicate dropwise, and continue stirring until the solution becomes clear to obtain a Silicalite-1 molecular sieve precursor solution; (2) Transfer the obtained solution into a stainless-steel autoclave equipped with a polytetrafluoroethylene liner, carry out hydrothermal crystallization at 190 °C for 48 h, perform suction filtration and drying to obtain a solid product of Silicalite-1 molecular sieve; (3) Heat the obtained solid product to 550 °C at a rate of 2 °C / min and calcine in air for 7 h to obtain plate-like Silicalite-1 molecular sieve; (4) Add 2.4 mg of aluminum isopropoxide into 20 mL of 0.2 M aqueous solution of tetrapropylammonium hydroxide and continuously stir until dissolved. Mix the obtained solution with 240 mg of the above-mentioned plate-like Silicalite-1 molecular sieve and transfer it into a stainless-steel autoclave equipped with a polytetrafluoroethylene liner, carry out homogeneous hydrothermal crystallization at 190 °C for 24 h, perform suction filtration and drying to obtain a solid product of hierarchical pore ZSM-5 molecular sieve; (5) Heat the obtained solid product to 550 °C at a rate of 2 °C / min and calcine in air for 7 h to obtain b highly interconnected hierarchical pore molecular sieve ZSM-5 single crystal nanosheets with shortened intra-crystalline

[0037] The intra-crystalline b shortened-axis hierarchical pore ZSM-5 molecular sieve (Si / Al ≈ 100) prepared by the above method has scanning electron microscope images and transmission electron microscope images as shown in Figure 1 and Figure 2 respectively, indicating that the obtained hierarchical pore ZSM-5 molecular sieve has a uniform nanosheet morphology and a rich intra-crystalline interconnected macropore-mesopore-micropore hierarchical structure, and the additionally introduced porous structure significantly shortens the diffusion distance of the intra-crystalline b axis (the shortest <000016I> axis length < 50 nm). The selected area electron diffraction image is as shown in Figure 3 and shows discrete single crystal diffraction spots of a typical MFI-type molecular sieve along the

[010] axis. The X-ray diffraction pattern is as shown in Figure 4 and has characteristic diffraction peaks of a typical MFI-type molecular sieve. The N2 adsorption-desorption isotherm is as shown in Figure 5 and shows that the obtained hierarchical pore ZSM-5 molecular sieve has both a rich microporous structure (P / P0 < 0.01) and a large number of etched macro-mesoporous structures (0.45 < P / P0 < 0.99), specifically a BET surface area of 409 m 2 / g, a microporous surface area of 163 m 2 / g, a total pore volume of 0.27 cm 3 / g and a microporous volume of 0.08 cm 3 / g. The silicon nuclear magnetic spectrum is as shown in Figure 6 and mainly contains Q 4 silicon Si(OSi)4 species at a chemical shift of about -113 ppm and a small amount of Q at -107 ppm3 Silicon Si(OSi)3(OH) or Si(OSi)3(OAl) species; aluminum NMR spectra such as Figure 7 As shown, all aluminum species were successfully incorporated into the molecular sieve framework and formed into tetrahedral aluminum AlO 4- The above NMR results all prove that the obtained hierarchical pore ZSM-5 molecular sieve has an extremely high degree of polycondensation.

[0038] Example 2 An intracrystalline b Preparation method of single crystal nanosheets of highly through-graded molecular sieve ZSM-5 with shortened axis: (1) Dissolve 1.90 g of urea in a mixed solution of 7.25 g of 2.0 M tetrapropylammonium hydroxide and 21.65 g of deionized water, add 16.50 g of tetraethyl orthosilicate dropwise, and continue stirring until the solution becomes clear to obtain a Silicalite-1 molecular sieve precursor solution; (2) The obtained solution was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, hydrothermally crystallized at 180°C for 60 h, filtered and dried to obtain a Silicalite-1 molecular sieve solid product; (3) The solid product was heated to 600°C at a rate of 3°C / min and calcined in air for 5 h to obtain a flat Silicalite-1 molecular sieve; (4) 15 mg of aluminum isopropoxide was added to 30 mL of 0.15 M tetrapropylammonium hydroxide aqueous solution and stirred continuously until dissolved. The resulting solution was mixed with 300 mg of the above-mentioned flat Silicalite-1 molecular sieve and transferred into a stainless steel autoclave lined with polytetrafluoroethylene. The mixture was homogeneously hydrothermally crystallized at 180 °C for 30 h, filtered and dried to obtain a hierarchical pore ZSM-5 molecular sieve solid product. (5) The solid product was heated to 600℃ at a rate of 3℃ / min and calcined in air for 5 h to obtain a low Si / Al crystal. b Axially shortened highly through-hole hierarchical pore molecular sieve ZSM-5 single crystal nanosheets.

[0039] The intracrystalline b The axis shortening grade pore ZSM-5 molecular sieve has a low Si / Al ratio of about 20, and its transmission electron microscope image is as follows Figure 8 As shown in Figure 2, it has a uniform nanosheet morphology and a rich intracrystalline through-hole macropore-mesopore-micropore hierarchical structure. Figure 9 As shown, it has typical MFI molecular sieve characteristic diffraction peaks.

[0040] Example 3 An intracrystalline bPreparation method of single crystal nanosheets of highly through-graded molecular sieve ZSM-5 with shortened axis: (1) Dissolve 2.90 g of urea in a mixed solution of 10.70 g of 2.0 M tetrapropylammonium hydroxide and 33.50 g of deionized water, add 25.10 g of tetraethyl orthosilicate dropwise, and continue stirring until the solution becomes clear to obtain a Silicalite-1 molecular sieve precursor solution; (2) The obtained solution was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, hydrothermally crystallized at 170°C for 72 h, filtered and dried to obtain a Silicalite-1 molecular sieve solid product; (3) The solid product was heated to 500°C at a rate of 2°C / min and calcined in air for 9 h to obtain a flat Silicalite-1 molecular sieve; (4) 3.8 mg of aluminum isopropoxide was added to 50 mL of 0.25 M tetrapropylammonium hydroxide aqueous solution and stirred continuously until dissolved. The resulting solution was mixed with 700 mg of the above-mentioned flat Silicalite-1 molecular sieve and transferred into a stainless steel autoclave lined with polytetrafluoroethylene. The mixture was homogeneously hydrothermally crystallized at 170 ° C for 36 h, filtered and dried to obtain a hierarchical pore ZSM-5 molecular sieve solid product. (5) The solid product was heated to 500℃ at a rate of 2℃ / min and calcined in air for 9 h to obtain a high Si / Al crystal. b Axially shortened highly through-hole hierarchical pore molecular sieve ZSM-5 single crystal nanosheets.

[0041] The intracrystalline b The axis shortening grade pore ZSM-5 molecular sieve has a high Si / Al ratio of about 200, and its transmission electron microscope image is as follows Figure 10 As shown in Figure 2, it has a uniform nanosheet morphology and a rich intracrystalline through-hole macropore-mesopore-micropore hierarchical structure. Figure 11 As shown, it has typical MFI molecular sieve characteristic diffraction peaks.

[0042] Comparative Example 1 A method for preparing hierarchical pore ZSM-5 molecular sieve nanoparticles, the specific steps are as follows: (1) 1.5 mL of 25 wt% tetrapropylammonium hydroxide, 10.0 mL of deionized water, and 1.5 mL of tetraethyl orthosilicate were mixed and stirred continuously until the solution became clear to obtain a Silicalite-1 molecular sieve precursor solution; (2) The obtained solution was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, hydrothermally crystallized at 180°C for 60 h, filtered and dried to obtain a Silicalite-1 molecular sieve solid product; (3) The solid product was heated to 550°C at a rate of 2°C / min and calcined in air for 6 h to obtain Silicalite-1 nanoparticles; (4) 3.6 mg of aluminum isopropoxide was added to 30 mL of 0.2 M tetrapropylammonium hydroxide aqueous solution and stirred continuously until dissolved. The resulting solution was mixed with 360 mg of the above-mentioned Silicalite-1 nanoparticles and transferred into a stainless steel autoclave equipped with a polytetrafluoroethylene liner. The mixture was homogeneously hydrothermally crystallized at 180 °C for 30 h, filtered and dried to obtain a hierarchical pore ZSM-5 molecular sieve solid product. (5) The solid product was heated to 550°C at a rate of 2°C / min and calcined in air for 6 h to obtain hierarchical pore ZSM-5 molecular sieve nanoparticles.

[0043] The scanning electron microscope image of the hierarchical pore ZSM-5 molecular sieve nanoparticles (Si / Al ≈ 100) prepared by the above method is shown in Figure 2. Figure 12 As shown, it has uniform grain size and abundant intracrystalline through-grade pore structure, but exhibits significantly shortened MFI. c Axis length and reduced MFI b The number of straight hole openings on the axis. Figure 13 As shown, it has typical characteristic diffraction peaks of MFI molecular sieves. It is worth noting that this comparative example further demonstrates the scalability and universality of the in-situ corrosion-recrystallization preparation strategy used in the present invention. By synthesizing silicon-containing templates of different sizes, shapes, and even structures (such as Silicalite-1 molecular sieve), combined with the structure-guiding and corrosion effects of tetrapropylammonium hydroxide, the prepared silicon-containing material can be used simultaneously as a template and silicon source to synthesize hierarchical pore molecular sieve catalytic materials with intracrystalline through-hole porous structures in a single step.

[0044] Comparative Example 2 A method for preparing nano ZSM-5 molecular sieve, the specific steps are as follows: 0.1 g of aluminum isopropoxide was dissolved in a mixed solution of 4.5 g of 25 wt% tetrapropylammonium hydroxide and 3.0 g of deionized water, and 10.4 g of tetraethyl orthosilicate was added dropwise and stirred continuously until clear. The resulting solution was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, aged at 80°C for 24 h, and then crystallized at 120°C for 48 h. The resulting solid product was filtered and dried, and then heated to 550°C at a rate of 1°C / min and air-calcined for 5 h to obtain nano ZSM-5 molecular sieve.

[0045] The scanning electron microscope image of the nano ZSM-5 molecular sieve (Si / Al ≈ 100) prepared by the above method is as follows: Figure 14 As shown, it has a uniform grain size.

[0046] Comparative Example 3 A method for preparing micron ZSM-5 molecular sieve, the specific steps are as follows: 0.1 g of aluminum isopropoxide was dissolved in a mixed solution of 5.5 g of 25 wt% tetrapropylammonium hydroxide and 20.0 g of deionized water, and 10.5 g of tetraethyl orthosilicate was added dropwise with continuous stirring. The resulting gel was transferred into a stainless steel autoclave lined with polytetrafluoroethylene and hydrothermally crystallized at 180°C for 72 h. The resulting solid product was filtered and dried, and then heated to 550°C at a rate of 3°C / min and air-calcined for 7 h to obtain a micron ZSM-5 molecular sieve.

[0047] The scanning electron microscope image of the micron ZSM-5 molecular sieve (Si / Al ≈ 100) prepared by the above method is as follows Figure 15 As shown, with MFI b The uniform coffin-like morphology with significantly increased axial thickness is b The average shortest diffusion length in the axial direction is about 1.6 μm, which is the average diffusion length in the crystal. b The axis shortening grade pore is more than 30 times that of ZSM-5 molecular sieve.

[0048] Application example: Methanol to olefins catalytic reaction 0.5 g of each ZSM-5 molecular sieve prepared in Examples 1-3 and Comparative Examples 1-3 was added to 12.5 mL of a 1.0 M aqueous ammonium nitrate solution and stirred in an 80°C oil bath for 5 hours. The resulting product was washed with deionized water and dried, then heated to 500°C in air at a rate of 2°C / min for 5 hours. This ammonia exchange process was repeated twice to obtain a series of H-type ZSM-5 molecular sieves.

[0049] 200 mg of the above series H-type ZSM-5 molecular sieve catalyst was pressed into a pellet and passed through a 40-60 mesh sieve, and then loaded into a fixed-bed quartz tube reactor with an inner diameter of 8 mm. Before the reaction began, the catalyst was activated at 500°C for 60 min in a 50 mL / min N2 atmosphere, and then the reaction temperature was adjusted to 480°C and maintained. The N2 flow rate was adjusted to 90 mL / min and flowed through a saturator containing methanol at 11.2°C to supply methanol vapor (weight hourly space velocity of 3.6 h / min). -1 ), and the reaction was initiated under atmospheric pressure. The product exiting the reactor was kept warm and analyzed by a Shimadzu 2014c gas chromatograph equipped with an Agilent Plot-Q column and an FID detector. Detailed catalytic reaction results are shown in Table 1.

[0050] Table 1

[0051] Note: 1Reaction time when methanol conversion rate is >95%; 2 Average ethylene + propylene selectivity with methanol conversion > 95%; 3 Percentage loss per hour from 95% to 50% methanol conversion; 4 The mass loss per gram of catalyst during the complete catalytic process.

[0052] From the results of methanol to olefins catalytic reaction shown in Table 1, it can be seen that the crystals b Axis shortened grade pore ZSM-5 molecular sieve (Example 1, the shortest intracrystalline b The axial diffusion length <50 nm) showed a significantly enhanced 63.5% double dilution selectivity and an extended 22.2 h catalytic life (methanol conversion rate >95%), which were 15% and 2.1 times higher than those of nano ZSM-5 molecular sieve (Comparative Example 2) and 19% and 6.5 times higher than those of micron ZSM-5 molecular sieve (Comparative Example 3). b The axial shortened pore ZSM-5 zeolite also showed the slowest average deactivation rate of 8.3% / h and the slowest average carbon deposition rate of 0.59 mg / g / h, indicating that the significantly shortened b The axial thickness gives it greatly enhanced mass transfer and diffusion capabilities and anti-carbon deposition deactivation kinetics. It is worth noting that the hierarchical pore ZSM-5 molecular sieve nanoparticles (Comparative Example 1) prepared using the same corrosion-recrystallization strategy also show better catalytic performance than nano ZSM-5 molecular sieve (Comparative Example 2) and micron ZSM-5 molecular sieve (Comparative Example 3). However, due to the shortened MFI c Axis length makes MFI b The number of axial straight channel openings is reduced, which is not conducive to the rapid diffusion of methanol and its reaction intermediates into and out of the micropores and contact with the acid active sites, resulting in a decrease in the number of axial straight channel openings compared to the crystal. b The axially shortened grade pore ZSM-5 molecular sieve (Example 1) has poor methanol to olefins catalytic performance.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. An intracrystalline b Axially shortened graded pore ZSM-5 molecular sieve, characterized in that The ZSM-5 molecular sieve is a single crystal nanosheet, comprising a highly interconnected hollow macropore-mesopore-micropore hierarchical structure; the overall size of the nanosheet is a : b : c = (600~800): (120~180): (4000~7000) nm; shortest intracrystalline b Axis diffusion length < 50 nm.

2. The intracrystalline b The preparation method of the hierarchical pore ZSM-5 molecular sieve with shortened axis is characterized in that The following steps are involved: (1) Dissolve urea in a mixed solution of tetrapropylammonium hydroxide and deionized water, add tetraethyl orthosilicate dropwise and continue stirring to hydrolyze until clear to obtain a Silicalite-1 molecular sieve precursor solution; (2) The obtained precursor solution was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and after hydrothermal crystallization, the solid product of pure silicon molecular sieve Silicalite-1 was obtained by filtration and drying; (3) The obtained pure silicon molecular sieve Silicalite-1 solid product is calcined at high temperature in air to obtain a flat Silicalite-1 molecular sieve; (4) Aluminum isopropoxide is dissolved in a tetrapropylammonium hydroxide aqueous solution, mixed with the obtained flat Silicalite-1 molecular sieve, and transferred into a stainless steel high-pressure reactor equipped with a polytetrafluoroethylene liner. After homogeneous hydrothermal crystallization, the mixture is filtered and dried to obtain a solid product of silicon aluminum molecular sieve ZSM-5; (5) The obtained solid product of silicon-alumina molecular sieve ZSM-5 is calcined in air to obtain the crystal b Axially shortened hierarchical pore ZSM-5 molecular sieve single crystal nanosheets.

3. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that In step 1, the molar ratio of urea, tetrapropylammonium hydroxide, deionized water and tetraethyl orthosilicate is (0.3-0.5): (0.15-0.21): (15-25):

1.

4. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that In step 1, the stirring hydrolysis temperature is 10-50°C and the time is 5-10 h.

5. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that The crystallization temperature of the hydrothermal crystallization treatment in step 2 is 160-200° C., and the crystallization time is 48-72 h.

6. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that In step 3, the calcination process is carried out by heating the material to 500-600°C at a rate of 1-5°C / min and keeping the temperature for 5-10 h.

7. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that In step 4, the concentration of the tetrapropylammonium hydroxide aqueous solution is 0.1-0.3 M; the mass ratio of the aluminum isopropoxide solution to the flat Silicalite-1 molecular sieve is between (0.005-0.05):1; and the liquid-to-solid ratio of the tetrapropylammonium hydroxide aqueous solution to the flat Silicalite-1 molecular sieve is between (70-90):1 mL / g.

8. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that The crystallization temperature of the homogeneous hydrothermal crystallization treatment in step 4 is 160~200℃, and the crystallization time is 24~48 hours.

9. The method for preparing the hierarchical pore ZSM-5 molecular sieve according to claim 2, characterized in that In step 5, the calcination process is carried out by heating the material to 500-600°C at a rate of 1-5°C / min and keeping the temperature for 5-10 h.

10. The intracrystalline b Application of ZSM-5 molecular sieve with shortened hierarchical pores in the catalytic reaction of methanol to olefins.